PERLINDUNGAN HUKUM BAGI PEMILIK OBJEK GADAI YANG DIGADAIKAN ORANG LAIN PADA PT. PEGADAIAN - NIRWANA DEWI HARAHAP (LP2MTBM MAKARIOZ, 2023)
Pegadaian is one of the State-Owned Enterprises in Indonesia. In carrying out its functions and duties pawnshops offer loans with a mortgage system. Crediting must be accompanied by a guarantee. Objects collateral in the form of moving goods that come from belonging to the pledgor or an owned sipemberi bip lien, however, that to be a problem if the pledgor ensure the property of others borrowed then mortgaged without the knowledge or permission of the owner of the goods that sesungguhnya. Permasalahan raised was First about how the guarantee procedure for the object does not belong to the pawn shop at PT. Pegadaian (Persero).Secondly, how is the auction execution of pawning against the collateral object that does not belong to the pledge giver at PT. Pegadai an (Persero), Third, How is the legal protection of the pledge object owner in the auction execution of mortgage.The research method used is an empirical juridical method with the nature of descriptive analysis.The data used skunder .Hasil primary data and research indicate that provisions of Article 1152 of the Civil Code which gives the possibility that the goods pawned for debt collateral material status is not moveable, but can also bergerak material owned by others. The guarantee procedure for the object of guarantee that is not owned by the pawn shop is the same as binding the object of legal guarantees as evidenced by the Proof of Credit. So everyone who comes to the PT. Personal identity.The auction continues while the pledge has defaulted on the agreement agreed in accordance with the provisions in the Credit Proof Letter. Legal protection for the owner of the collateral pledge object which is actually on the auction of a pawn object is given by law namely if it is proven that the pawn recipient receives a pawn in a bad faith, then the pledge recipient is obliged to return the pawned goods to the real owner. Completion of this case demands from the owner of the object the real guarantee to PT. Pegadaian is not granted because in this case the real owner has no legal protection.